A finite-difference and Haar wavelets hybrid collocation technique for non-linear inverse Cauchy problems. Issue 1 (2nd January 2022) - Ahsan, Muhammad; Hussain, Iltaf; Ahmad, Masood
Abstract : In this research work, a finite-difference and Haar wavelet hybrid collocation scheme is introduced for the ill-posed non-linear inverse Cauchy problem with a source depending on space variable along with an unknown solution and unknown right side boundary. The first-order finite-difference approach is adopted to approximate the ∂ u ∂ t part and two different Haar series are managed to approximate ∂ 2 u ∂ x 2 part and source term respectively. A simple linearization procedure is used to convert the non-linear problem into a linear form. In contradiction to various numerical schemes, the current introduced method generates a well-conditioned system of algebraic equations, therefore it is not required to apply a regularization approach. The results of the proposed method are stable and converge to the exact solution. Some numerical tests are also performed to confirm the accuracy, well-conditioning of the algebraic equations and easy applicability of the scheme on linear and non-linear cases.